2005
DOI: 10.1111/j.1365-2699.2005.01348.x
|View full text |Cite
|
Sign up to set email alerts
|

The importance of species identity in the biocontrol process: identifying the subspecies of Acacia nilotica (Leguminosae: Mimosoideae) by genetic distance and the implications for biological control

Abstract: Aims A molecular genetic distance study has been used in an initial survey to identify subspecies and genotypes of the weed Acacia nilotica in Australia, information needed to find suitable biocontrol agents. We use patterns of DNA sequence variation (in two DNA fragments) from each of the nine described subspecies of Acacia nilotica (L.) Delile (Leguminosae: Mimosoideae) that is to determine their genetic similarity, to verify if the Australian populations are A. nilotica ssp. indica (Benth.) Brenan, and to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 37 publications
1
31
1
Order By: Relevance
“…data 2005). This finding supports the need to search for coevolved biological control agents in India and Pakistan (Anonymous 1995;Wardill et al 2005).…”
Section: Plant Genotypesupporting
confidence: 83%
See 1 more Smart Citation
“…data 2005). This finding supports the need to search for coevolved biological control agents in India and Pakistan (Anonymous 1995;Wardill et al 2005).…”
Section: Plant Genotypesupporting
confidence: 83%
“…Genetic studies have revealed that the invasive prickly acacia population in Australia is the subspecies A. nilotica indica, which is native to India and Pakistan (Wardill et al 2005). This is further supported by plant morphological (Brenan 1983) and biochemical (Hannan-Jones 1999) studies.…”
Section: Plant Genotypementioning
confidence: 97%
“…In Africa, there have been three major phylogeographic studies of African tree species found in these biomes. A study of Acacia nilotica populations showed genetic differences that broadly matched subspecific designations and a phylogeographic separation of North and West Africa from East and Southern Africa (Wardill et al, 2005). The other two studies, of the baobab tree (Adansonia digitata L., Malvaceae; Pock Tsy et al, 2009) and the shea tree (Vitellaria paradoxa C. F. Gaertn, Sapotaceae; Allal et al, 2011) showed strong phylogeographic structure, distinguishing Eastern and Western populations within the Sudano-Sahelian region.…”
Section: Introductionmentioning
confidence: 95%
“…Two DNA fragments, the trnL and the ITS-1, were used to identify eight of nine described subspecies of A. nilotica (L.) Delile and to report a previously unknown genotype from Pakistan (Wardill et al 2005). The study also indicated that the populations of this plant that are very serious weeds in Australia are mainly A. nilotica ssp.…”
Section: Where To Search: Determining the Native Range And Origin Of mentioning
confidence: 98%